Penerapan Kompres Rebusan Jahe Terhadap Penurunan Skala Nyeri Pada Lansia Osteoarthritis di Kelurahan Jebres - Arifah Fani Hastuti; Tri Susilowati (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Background : Based on the WHO suevey around 529 million people around the world suffer from osteoartgritis. In Indonesia people who ferment arthritis disease numer 181,556. Osteoarthritis is a chronic, progressive joint disorder that typically occurs in middle to old age with reference to cartilage damage located in bone joints. In osteoarthritis a deterioration of the caetilage tissue in the joint region will result in pain and rigidity that lead to motion impairment. Non pharmalogical therapy is recommended with steaming giner stew. Objective The ginger stew therapy is for lowering the scale of pain in oldet osteoarthritis. Method : The research used was a descriptive study using case study methods. The subject pf the board’s diagnosis is two osteoarthritis respondens. Result : A case dtudy has shown that there has been a decline in the scare of pain in older osteoarthritis. Conclusion : The progression of the scales of pain before and after application of the ginger stew made 2 respondents had a decrease I the scale of the pain with a 2-3 scale